Eight-year chronic wound caused by Tarlov’s cyst: a case report - Ya-Ning Huang; I-Wei Chang; Sung-Tse Li; Wei-Te Lei (Journal of Medical Case Reports, 2023)
Abstract Background Tarlov’s cyst is often underdiagnosed since it is difficult to identify without imaging assistance. Herein, we report the case of a young girl who presented with an 8-year history of chronic osteomyelitis of bilateral proximal phalanges and metatarsal bones caused by a Tarlov’s cyst that did not contain a nerve root. The chronic wound in the forefoot is an unusual presentation and resulted from the Tarlov’s cyst accompanied with tethered conus syndrome. Case presentation A 10-year-old Asian girl presented with an 8-year history of chronic osteomyelitis of bilateral proximal phalanges and metatarsal bones. She received sequestrectomy five times, however the immune function tests were all normal. A neurological examination revealed diminished sensation and a slapping gait pattern. Magnetic resonance imaging (MRI) demonstrated a lobulated cyst at the right aspect of the sacrum (S) 1 to sacrum (S) 3 canal near the dorsal root ganglion. Tethered conus syndrome was highly suspected. She received laminectomy of lumbar (L) 5 and S1–S2, which led to the diagnosis of a right S1–S3 epidural cyst. The final diagnosis from the histopathological examination was a right sacral Tarlov’s cyst. The clinical conditions of diminished sensation and slapping gait pattern greatly improved after successful surgical treatment. Conclusion In children who present with a recalcitrant chronic wound in the forefoot accompanied with a slapping gait pattern and foot hypoesthesia to pain, aggressive imaging examinations such as spine MRI should be arranged for further evaluation, especially in immunocompetent children.